Design of Secure Transmission of Multimedia Data Using SRTP on Linux Platform - Shashidhar H.G.; Sanket Dessai; Shilpa Chaudhari (International Journal of Reconfigurable and Embedded Systems (IJRES), 2015)
This paper aims for providing a viable solution for security in streaming media technology. Service providers do not want the end users to capture and duplicate streaming media data. Once captured data can be re-distributed to millions without any control from the source.  Licensing issues also dictate the number of times end user may utilize the data. Encryption is not sufficient as it leaves the system vulnerable to duplication and recording after decryption. In this paper an attempt has been made to transmit digital multimedia data to multiple users. The transmission of the video/audio data has been attempted from one PC to another PC. While doing this, security considerations have to be taken care by using suitable encryption/decryption techniques.  A research carried out on the different data transmission protocols reveals that the Secure Real Time Transport Protocol (SRTP) is one of the best available protocols. Hence the SRTP has been deployed in this project on Linux OS using socket programming. The code for the transmitter and the receiver is designed and developed around the SRTP library for transmission of multimedia data.  The solution is illustrated by choosing an example of a video clip for transmission and reception. This model increasing the security of streaming media and adds a measure of integrity protection, but it is primarily intended to aid in replay preventions.